(untitled) (Research, Society and Development, 2021)
In the classic theories about Human Rights, these are thought to stem from a certain "human nature", in the sense that such rights would immediately be derived from a founding dignity of the "human" category. Such a simple statement, however, is paradoxical with the immense difficulty in guaranteeing human rights to entire communities, especially when exclusionary ways of understanding the human are in operation, linked to nationalisms, racializations, or to experiences of gender and sexuality understood as “deviants”. In the latter, the paradox of human nature is shown in its crudity, given that the experiences of LGBTI + groups have historically been identified as “unnatural”. The demands for rights of LGBTI + people, therefore, have been accompanied in the world context by a demand to integrate the category of the human, including appealing, in some cases, to bio-ontological understandings of the definition of human sexuality as a key argument. Such a posture has the evident objective of naturalizing the LGBTI + experience, thus disputing which bodily and sexual experiences the category of the human can “naturally” contain. With the aim of exploring and questioning the narrated reality and through an essayist-based methodology, this article demonstrates that such a movement shows a paradox: while the foundation in human nature is often placed as a way to protect the rights of exclusionary and reductionist tendencies, it is in itself exclusionary, in the sense that "human nature" does not have a unique ontological meaning to be discovered, but is itself socially defined. In developing this problem, this work seeks to dialogue with perspectives of contemporary philosophy, and specially with Judith Butler’s work, which show us that all ontology, especially that related to sexual and gender identities, is historical. So is “human nature”, and it is necessary to question the meanings it occupies as the foundation of human rights. In a provisory conclusion, it is proposed to think about human rights from contingent foundations, in the sense brought by Butler, which, in order to fulfill their role of expanding livable forms of life, must always remain open to contestation and to the expansion of their borders, including new human experiences.